Criteria to set conservation priorities for natural areas in the Sinaloa region, Mexico - Amador-Cruz, Francisco; Bordenave, Bruno George (BOSQUE, 2024)
To identify Conservation Priority Sites (CPS), several models are currently available, using geographic information systems, mathematical algorithms or more traditional field methods among which the Determination Index (DET) method using a set of criteria, Specific Diversity Index, Ratio of Species of Concern, Relative Scarcity Index and Habitat Fragility Index to assess conservation stakes over wild plant species and habitats patterns. The aim of this study is to establish CPS in the southern Sinaloa region, Mexico using the DET method. In 2017 eight sampling sites were assessed, two in mangroves, three in dry forest and three in semi-deciduous forest, each 0.12 ha in surface area. Species-area curves were analysed to quantify species diversity. The ratio of species of concern was calculated using a Floristic Originality Index. A relative scarcity index was calculated from each type of vegetation surface area. Fragility of habitats was estimated over five levels of resilience. The resulting DET evidences semi-deciduous forest sites as the highest conservation priorities, due to higher species diversity values, number of species of concern and scarce surface. DET method enabled the ranking of CPS in the study area, moreover, it is recommended as a useful tool for natural and anthropized landscape planning and over conservation patterns.